Effect of compatibilizer on the dynamic mechanical and electrical properties of kaolin clay reinforced EPDM rubber - Gautam Sarkhel,; Sanjay Manjhi, (Universiti Kebangsaan Malaysia, 2013)
Industrial pollution issue and dark colour of carbon black, clay based non black filler are getting more importance for reinforcing elastomer. EPDM-Kaolin composites with various maleated EPDM concentration have been prepared by mixing on a two roll mill. The rheometry data showed the optimum cure time increases with increasing compatibilizer concentration without decreasing torque value indicating that acidic functional groups comes from compatibilizer could retard cure rate and increase the optimum cure time rather than change in the ultimate cure state. As the filler concentration increases, the edge to edge and face to edge interaction between filler and EPDM increases and the free volume between EPDM molecules is reduced, the storage modulus increases. Moreover, the dynamic mechanical analysis also showed the increase in glass transition temperature with increase in filler concentration due to the inter-tubular diffusion of EPDM inside the clay. It was also observed that with increasing filler concentration, the resistivity and dielectric strength decreases and moreover with increasing compatibilizer concentration the resistivity decreases due to better dispersion of filler helps to build conduction path. The morphological study also revealed that homogeneity of filler dispersion increases with increase in compatibilizer concentration.